Vancomycin dosing, monitoring and toxicity: Critical review of the clinical practice - Zamoner, Welder [UNESP]; Prado, Iara Ranona Sousa [UNESP]; Balbi, André Luis [UNESP]; Ponce, Daniela [UNESP] (Wiley, 2019)
Vancomycin is an antibiotic used in the treatment of infections caused by multidrug-resistant Gram-positive bacteria, especially methicillin-resistant Staphylococcus aureus. In the last decades, vancomycin has been widely used in hospital environments due to the increasing incidence of sepsis and septic shock. Sepsis may lead to multiple organ failure; it is considered a risk factor for the development of acute kidney injury (AKI), with an overall mortality rate of around 45%, which can reach the surprising rate of 70% with the combination of AKI and sepsis. Considering the high mortality rate of sepsis and its related costs of hospitalization and treatment, specific measures should be adopted, such as early-goal treatment protocols: proper and early administration of antimicrobials, fluids, vasoactive drugs and transfusion support. Besides the careful selection of the antimicrobial, another concern related to critically ill patients is the proper dose of the antimicrobial, since pharmacokinetic changes are observed due to drug absorption, distribution, metabolism and elimination. Gram-positive pathogens are very common in hospitalized patients with septic shock, so vancomycin has been the antimicrobial of choice for more than 60 years. However, discussions about its dosage, administration and monitoring are extremely important, considering the risk of nephrotoxicity and the emergence of resistant S. aureus. This narrative review aims to discuss controversial aspects related to the efficacy and safety of vancomycin, correlating them with data available in the literature and identifying knowledge gaps in guide future lines of research.
Keywords: acute kidney injury; efficacy; nephrotoxicity; pharmacodynamics; pharmacokinetics; safety; sepsis; vancomycin